Temporal dynamics of learning-promoted synaptic diversity in CA1 pyramidal neurons - Sakimoto, Yuya (FASEB J, 2019)
Although contextual learning requires plasticity at both excitatory and inhibitory (E/I) synapses in cornu ammonis 1 (CA1) neurons, the temporal dynamics across the neuronal population are poorly understood. Using an inhibitory avoidance task, we analyzed the dynamic changes in learning-induced E/I synaptic plasticity. The training strengthened GABA(A) receptor–mediated synapses within 1 min, peaked at 10 min, and lasted for over 60 min. The intracellular loop (Ser(408−409)) of GABA(A) receptor β(3) subunit was also phosphorylated within 1 min of training. As the results of strengthening of α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor–mediated synapses, CA1 pyramidal neurons exhibited broad diversity of E/I synaptic currents within 5 min. Moreover, presynaptic glutamate release probability at basal dendrites also increased within 5 min. To further quantify the diversified E/I synaptic currents, we calculated self-entropy (bit) for individual neurons. The neurons showed individual levels of the parameter, which rapidly increased within 1 min of training and maintained for over 60 min. These results suggest that learning-induced synaptic plasticity is critical immediately following encoding rather than during the retrieval phase of the learning. Understanding the temporal dynamics along with the quantification of synaptic diversity would be necessary to identify a failure point for learning-promoted plasticity in cognitive disorders.—Sakimoto, Y., Kida, H., Mitsushima, D. Temporal dynamics of learning-promoted synaptic diversity in CA1 pyramidal neurons.